2022
DOI: 10.5194/acp-2021-1050
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The representation of winds in the lower troposphere in ECMWF forecasts and reanalyses during the EUREC4A field campaign

Abstract: Abstract. The characterization of systematic forecast errors in lower-tropospheric winds over the ocean is a primary need for reforming models. Winds are among the drivers of convection, thus an accurate representation of winds is essential for better convective parameterizations. We focus on the temporal variability and vertical distribution of lower-tropospheric wind biases in operational medium-range weather forecasts and ERA5 reanalyses produced with the Integrated Forecasting System (IFS) of the European … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 23 publications
2
23
0
Order By: Relevance
“…In particular, it seems that the numerical model of the reanalysis underestimates the change in stability over the cold water, producing a too weak reduction of vertical mixing. This can be ascribed to the difficulties that the ABL numerical scheme has in correctly reproducing the lower atmospheric mixing, which is likely to be responsible for the observed wind biases (Savazzi et al., 2022). Different ABL numerical schemes produce different mixing, resulting in different air‐sea coupling (Perlin et al., 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, it seems that the numerical model of the reanalysis underestimates the change in stability over the cold water, producing a too weak reduction of vertical mixing. This can be ascribed to the difficulties that the ABL numerical scheme has in correctly reproducing the lower atmospheric mixing, which is likely to be responsible for the observed wind biases (Savazzi et al., 2022). Different ABL numerical schemes produce different mixing, resulting in different air‐sea coupling (Perlin et al., 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Even if Savazzi et al. (2022) showed that the assimilation of RS data is negligible on the wind field, the reanalysis fields should not be considered as independent data but as a physically based spatio‐temporal interpolation of the observations. Reanalysis data can be used to estimate the large‐scale variability signal to isolate the local one better.…”
Section: Methodsmentioning
confidence: 99%
“…{7}^{\circ } $$ and at 20 height levels between 100 and 2,000 m, with one scan roughly every 30 s. The radial velocities were corrected for ship motions using an accompanying GPS system, described in Savazzi et al . (2021). After motion correction, the wind vector is retrieved and hourly averages are used to study the composite diurnal cycle.…”
Section: Eurec4$$ {}^4 $$A/atomic Datamentioning
confidence: 99%
“…Operational high‐resolution (9 km) forecasts from the IFS as well as ERA5 reanalysis are used to assess the synoptic situation during EUREC4$$ {}^4 $$A/ATOMIC and evaluate the pressure gradient force and advection terms derived from the circular dropsonde arrays. For the forecast, model output was extracted at the nearest four neighbours of 61 points placed concentrically around the center of the EUREC4$$ {}^4 $$A/ATOMIC circle, matching the flight hours on flight days (Savazzi et al ., 2021). ERA5 data are extracted for an area 65°–25°W and 0°–30°N encompassing Barbados.…”
Section: Eurec4$$ {}^4 $$A/atomic Datamentioning
confidence: 99%
See 1 more Smart Citation